Student demand survey for entrepreneurship education in art and design universities: A kano model approach - Min, Wang; Jie, Song (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to apply the Kano model to conduct an in-depth analysis of the demand characteristics of art and design university students for entrepreneurship education functions and services, providing scientific evidence for optimizing entrepreneurship education systems. Using a questionnaire survey method, 205 art and design students were selected as research subjects, and a Kano model questionnaire containing 15 entrepreneurship education functions was constructed. Through positive and negative item design, student demand attribute classifications were identified. SPSS was used for reliability and validity testing and data analysis. The study found that digital platform skills training, international entrepreneurship exchange resources, dedicated entrepreneurship offices, and professional entrepreneurship courses were classified as must-be attributes; student artwork commercialization platforms, industry mentor guidance, funding application training, university-enterprise cooperation projects, psychological counseling mechanisms, and entrepreneurship competitions belong to attractive attributes; entrepreneurship achievement exhibitions, legal knowledge courses, and business model content are one-dimensional attributes; portfolio guidance and interdisciplinary team platforms are indifferent attributes. Art and design universities should prioritize the construction of must-be attribute functions, focus on developing attractive attribute projects, and reasonably allocate one-dimensional attribute resources to improve entrepreneurship education quality and student satisfaction. This research provides empirical support for constructing entrepreneurship education systems that align with the characteristics of art and design disciplines.